Can patriotism be a protective factor for symptoms of post-traumatic stress disorder? The case of the Russia – Ukraine 2022 war. (November 2022) - Hamama-Raz, Yaira; Goodwin, Robin; Leshem, Elazar; Ben-Ezra, Menachem
Abstract: The 2022 Russian invasion of the Ukraine created a large-scale humanitarian crisis that has intensified as the conflict persists. The impact of armed conflict, such as forced migration, exposure to violence, supply shortages, destruction of infrastructure, and interruption of essential services, can have serious negative consequences for the mental health and wellbeing of Ukrainians living through the invasion and its aftermath. At the same time threat to a nation can trigger a wave of patriotism. Such feelings of patriotic belonging, love, pride and caring for a country can help maintain national group cohesion and respect for civic authorities. We studied demographic and war related factors associated with patriotic attitudes and posttraumatic stress disorder (PTSD) symptoms in a national Ukraine sample of 2000 respondents six weeks into this crisis. Respondents completed an online inventory assessing patriotic attitudes, PTSD symptoms, having relatives wounded or killed, having relatives who left Ukraine due to the war, alongside key demographics. Hierarchical regressions found that having relatives that were wounded or that left Ukraine because of the war and those coming from a Ukrainian speaking region were associated with patriotic attitudes. Patriotic attitudes were positively associated with elevated risk for PTSD symptoms. Mental health professionals should consider the potential mental health burden of existential national conflicts amongst civilian populations with strongly patriotic attitudes. Highlights: We examined patriotism amongst a national sample of 2000 adults in Ukraine six-weeks into the Russian invasion (2022). Region of Ukraine and having relatives that were wounded or had left the country were associated with patriotic attitudes. Patriotic attitudes were positively associated with an elevated risk for PTSD symptoms. Health professionals need to be aware of the association between PTSD and patriotism when designing interventions during intense national conflict.